New synonymies, new combinations and lectotype designations for weevils in the tribe Naupactini (Coleoptera: Curculionidae: Entiminae) - Río, M. Guadalupe Del; Lanteri, Analía A. (Zootaxa, 2018)
We examined the type material of 15 species of Naupactus Dejean and related genera (Curculionidae: Entiminae), most of them described by Alphonse Hustache (Museum National d’Histoire Naturelle, Paris) and Carl Boheman (Naturhistoriska Riksmuseet, Stockholm). The information associated with the types was compared with the original descriptions, and large series of specimens were examined in order to analyze the variation of each species throughout its range (sexual dimorphism, other kinds of polymorphism or geographic variation). Based on the results of this study we establish seven new combinations, one new placement and nine new synonymies, we make 21 lectotype designations and provide three new country and state records. Alceis curtus (Boh.), Lanterius leucophaeus (Boh.), L. sparsus (Boh.), L. sellatus (Boh.), Parapantomorus carinirostris (Hust.), Symmathetes signatus (Blanchard) and Teratopactus acerbus (Boh.) are new combinations and T. sulphureoviridis Hust. is a new placement. The following names are senior synonyms of those between parentheses: Lanterius inermis (Hust.) (syn. Macrostylus ocellatus Lanteri); Naupactus auricinctus Boh. (syn. N. ruficornis Boh.); N. bridgesii G.R. Waterhouse (syn. N. angulithorax Hust.); N. condecoratus Boh. (syn. N. bosqi Hust.); N. cyphoides (Heller) (syn. N. calamuchitanensis Hust., N. viridinitens Hust, N. viridulus Hust.); N. peregrinus (Buchanan) (syn. N. brevicrinitus Hust.); and Trichonaupactus densior Hust. (syn. T. rexus Hust.). For each species we provide the following information: synonyms, available data on type specimens (sex, body length, geographic location, kind of type, and repository), complete geographic distribution, pictures of types or specimens compared with types, an explanation about the reasons that justify the nomenclatural acts.